Rethinking FDI Policy in Bangladesh: An Asymmetric Approach to Globalization, Population, and Trade - Biswas, Al Amin; Shahriar, A. H. M.; Alam, Mohammad Jahangir; Kuddus, Ruhul; Golder, Uttam; Paul, Mita Rani (International Journal of Economics and Financial Issues, 2023)
Prior studies in Bangladesh were conducted to examine either the impact of globalization on the foreign direct investments (FDI), population growth on the FDI, or trade openness on the FDI. No studies were conducted to examine the combined effects of those variables on the FDI. Besides, most of the studies conducted used linear models and almost no studies were done to see the non-linear effects. This study thereby attempts to check the asymmetric effects of globalization, population growth, and trade openness on the FDI of Bangladesh taking time series from 1990 to 2020. The study used the NARDL model to see the long run effects of the explanatory variables on the responding variable. The asymmetric association is confirmed by study results. The results show that rising globalization is not good for growth of the FDI rather the opposite is better. The uniqueness of the study is that both increase or decrease in population boosted the FDI of the country. However, decrease in trade openness brought the FDI down. So, the government should take necessary steps to boost the imports and exports of the country, and to tackle ripple effects of global crisis causing due to globalization.